Integrated science 2 - Bethell, George; Coppock, David ([S.l.] : Oxford University Press, 1991)
Part of a series designed for KS4 of the National Curriculum for Science (Model A and B), the text may be used with GCSE integrated science courses. The series consists of students' and teachers' book for Parts 1 and 2. Containing many everyday applications of scientific principles, this GCSE textbook provides balanced views of such important issues as personal health, environmental pollution and nuclear power. It also contains appropriate experimental work and worked examples, accompanied by illustrations.
Keywords: science